Serum platelet factor 4 is a reliable activity parameter in adult patients with inflammatory bowel disease: A pilot study. Issue 11 (March 2017) - Ye, Lei; Zhang, Yu-Ping; Yu, Na; Jia, Ya-Xu; Wan, Shu-Jun; Wang, Fang-Yu
Abstract : Abstract: To investigate the diagnostic utility of serum platelet factor 4 (PF4) levels and to assess its accuracy in detecting inflammatory bowel disease activity. This study included 45 patients with ulcerative colitis (UC), 45 patients with Crohn disease (CD), and 30 control subjects at Jinling Hospital between May 2014 and July 2015. Laboratory tests measured white blood count, C-reactive protein, erythrocyte sedimentation rate, and platelet count. PF4 was examined by enzyme-linked immunosorbent assays. Patients were divided into 2 groups according to disease activity: active and inactive. Median PF4 values dramatically increased in UC and CD patients compared with the healthy group (UC: 26.64 [20.00–36.22] mg/mL vs 20.02 [14.63–26.83] mg/mL, P  = 0.002; CD: 25.56 [18.57–36.36] mg/mL vs 20.02 [14.63–26.83] mg/mL, P  = 0.014); however, the serum PF4 levels between UC and CD failed to show a significant difference (26.64 [20.00–36.22] mg/mL vs 25.56 [18.57–36.36] mg/mL, P  = 0.521). Furthermore, serum PF4 levels were elevated in both UC and CD patients with active disease (UC: 20.19 [14.89–23.53] mg/mL vs 28.86 [22.57–37.29] mg/mL, P  < 0.001; CD: 18.33 [16.72–25.77] mg/mL vs 34.38 [22.58–39.92] mg/mL, P  < 0.001). Multivariate analysis revealed higher PF4 level as an independent predictor of disease activity in UC and CD patients (UC: odds ratio 30.375, P  = 0.002; CD: odds ratio 54.167, P  < 0.001). The cut-off level of PF4 for distinguishing active from inactive UC patients was 24.1 mg/mL. While in CD patients, the cut-off level of PF4 was 19.24 mg/mL. Serum PF4 levels could be a potential biomarker for monitoring the disease activity of inflammatory bowel disease. Abstract : Supplemental Digital Content is available in the text